(untitled) (Innovaciones Educativas, 2023)
This work analyses Neurolinguistic Programming (NLP) as a communication strategy that improves the students’ internal strengths and enhances their intrapersonal skills, positively affecting their learning process and academic performance in Virtual Learning Environments (VLE). Likewise, the population for this study comprises students of the ECA-UNED Marketing Chair enrolled during the third quarter of 2021. This way, a quantitative research approach is carried out with an experimental and correlational design. Moreover, students select the answer with the highest level on the Likert scale before the indicators that measure the interpersonal skills of the experimental group. As a result, they obtained a higher average percentage, comparatively, with the control group, which shows a significant difference in favor of the experimental group that underwent NLP techniques. Because of the results, it is concluded that Neurolinguistic Programming positively affects students’ intrapersonal skills in indicators such as self-motivation, self-performance, self-regulation, and self-control, among others. Furthermore, PNL is also an excellent communication strategy for working collaboratively in interaction with the facilitators and VLE students.